Pemberian ekstrak daun sirih (Piper betle) secara topikal meningkatkan ketebalan epidermis, jumlah fibroblas, dan jumlah kolagen dalam proses penyembuhan luka pada tikus jantan galur Wistar (Rattus norvegicus) - Palumpun, Eva F.; Wiraguna, Anak A.G.P.; Pangkahila, Wimpie (Universitas Sam Ratulangi, 2017)
Abstract: This study was aimed to prove that topical betel (Piper betle) leaf extract adinistration could increase epidermal thickness, fibroblasts, and collagen amount in wound healing process of male Wistar rats (Rattus norvegicus). Subjects were 36 Wistar rats (Rattus norvegicus) with inclusion criteria, as follows: healthy, aged 3-4 months, weighing 200-250 g, divided into two groups with 18 rats each. The first group, the control group (P0), was treated with oral amoxicillin 3x10mg/day for 3 days and one drop (50 μl) of 10% povidine iodine topically 2x/day for 14 days, and the second group, the treatment group (P1), treated with oral amoxicillin 3x10 mg/day for 3 days and one drop (50 μl) of 10% betel leaf (Piper betle) extracttopically 2x/day for 14 days. Samples of skin tissue were processed for histological slides by using hematoxylin-eosin staining to check the epidermal thickness and fibroblast, meanwhile Picro sirius red staining to check the collagen amount. Microscopic examinations showed that the average epidermal thickness in P0 group was 24.72±14.91 μm, whereas in the P1 group was 56.75±23.04 μm (P <0.01). The number of fibroblasts in P0 group was 75,45±32,52 cells/visual field meanwhile of P1 group was 95,67±22,51 cells/visual field (P < 0.05). The average of collagen amount in P0 group was 65.27±7.13% while in P1 group was 83.09±2.59% (P <0.01). Conclusion: Topical administration of 10% betel (Piper betle) leaf extract could increase epidermal thickness, fibroblasts, and collagen in wound healing process of male Wistar rats (Rattus norvegicus).Keywords: betel leaf, epidermis, fibroblast, collagen, wound Abstrak: Tujuan penelitian ini ialah untuk membuktikan bahwa pemberian ekstrak daun sirih (Piper betle) meningkatkan ketebalan epidermis, jumlah fibroblas, dan jumlah kolagen dalam proses penyembuhan luka pada tikus jantan galur Wistar (Rattus norvegicus). Subjek penelitian ialah 36 ekor tikus jantan galur Wistar (Rattus norvegicus) dewasa dan sehat, berumur 3-4 bulan, dengan berat badan 200-250 gr, yang terbagi menjadi 2 (dua) kelompok masing-masing berjumlah 18 ekor tikus. Kelompok pertama ialah kelompok kontrol (P0) diberikan amoksisilin oral 3 x 10mg/hari selama 3 hari serta povidine iodine 10% topikal 1 tetes (50 μl) 2x/hari selama 14 hari (P0). Kelompok kedua ialah kelompok perlakuan (P1) diberi amoksisilin oral 3 x 10 mg/hari selama 3 hari serta ekstrak daun sirih (Piper betle) konsentasi 10% secara topikal 1 tetes (50 μl), 2x/hari selama 14 hari. Jaringan kulit diambil dan dibuat preparat dengan pewarnaan hematoksilin-eosin untuk pemeriksaan ketebalan epidermis dan jumlah fibroblas, serta pewarnaan Picro sirius red untuk pemeriksaan jumlah kolagen. Hasil pemeriksaan mikroskopik menunjukkan rerata tebal epidermis pada kelompok P0 24,72±14,91 μm dan pada kelompok P1 56,75±23,04 μm (P <0,01). Rerata jumlah fibroblas pada kelompok P0 75,45±32,52 sel/lapang pandang dan pada kelompok P1 95,67±22,51 sel/lapang pandang (P <0,05). Rerata jumlah kolagen pada kelompok P0 65,27±7,13% dan pada kelompok P1, 83,09±2,59% (P <0,01). Simpulan: Pemberian ekstrak daun sirih (Piper betle) konsentrasi 10% secara topikal dapat meningkatkan ketebalan epidermis, jumlah fibroblas, dan jumlah kolagen pada luka tikus jantan galur Wistar (Rattus norvegicus). Kata kunci: daun sirih, epdermis, fibroblas, kolagen, luka